2020
DOI: 10.1155/2020/1847159
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline‐Induced Cardiotoxicity in Breast Cancer Patients from Southern Sri Lanka: An Echocardiographic Analysis

Abstract: Anthracycline-induced cardiotoxicity has never been investigated in Sri Lanka. Therefore, this study was conducted to determine the prevalence of anthracycline-induced cardiotoxicity in breast cancer patients using echocardiographic findings. A prospective cohort study was performed. All newly diagnosed breast cancer patients who were administered with anthracycline and cyclophosphamide (AC schedule) for the first time were enrolled in the study. In the hospital setting, anthracycline is administered only as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Table 1 showed the demographic data and clinical characteristics of patients 16–59 . Cancer type, treatment, and imaging technique for each study are reported in Table 2 16–59 . Patient population ranged from 28 to 2625 subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 showed the demographic data and clinical characteristics of patients 16–59 . Cancer type, treatment, and imaging technique for each study are reported in Table 2 16–59 . Patient population ranged from 28 to 2625 subjects.…”
Section: Resultsmentioning
confidence: 99%
“…This is lower compared to the results from other studies done in Asia where the incidence ranged from 25% to 33%. This may in part be due to the use of varying definitions of AIC [ 13 , 15 , 16 ]. In this study, the investigators strictly followed the definition of the American and European Society of Echocardiography Expert Consensus of Anthracycline-induced cardiotoxicity, which is a reduction of LVEF by more than 10%, to a value below 53% [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A minimum of 340 breast cancer patients were required for this study based on a level of significance of 5%, assuming that 33.16% [ 13 ] of patients will develop cardiotoxicity, with the desired width of CI (precision) of 10% [ 14 ] as noted from the reference article by Sandamali et al, 2020 [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…CP exposure in the myocardial cell is responsible for an increase in the formation of NO due to the activity of eNOS and iNOS. On myocardial cells, eNOS and iNOS have been shown to have both protective and toxic effects [ 31 , 32 ]. The protective effect is due to the formation of NO, but generated NO when reacting with oxygen free radicals generates peroxynitrite (ONOO − ), which is responsible for the toxic effects on the myocardial cell.…”
Section: Mode Of Cardiotoxicity Inductionmentioning
confidence: 99%